Prakarya Membuat Mainan Anti Korupsi - Ihsan, Mohammad; Prasetya Gunawan , Irwan; Hatta, Holila (LPkM Universitas Bakrie, 2019)
This study is based on Community Service Activities (PkM) conducted by the Bakrie University PKM Team which was held on Saturday, January 5, 2019 in Kaliurang Village, Yogyakarta. Participants in the activity are elementary school-age children, and the material provided to them is in the form of knowledge about anti-corruption culture through two series of activities: 1) making various kinds of craft / toy models; and 2) anti-corruption game activities using toys / mockups that have been made. All of this was done so that the training participants whose meetings consisted of elementary school-aged children get a pleasant atmosphere so that they can receive learning materials properly. Through the experience of interacting with others, children will learn to understand which activities or behaviors are good / allowed / accepted / approved or bad / cannot / rejected / disapproved. It is hoped that with a good and appropriate learning model, the moral of the nation's future generation who will be anti-corruption, good behavior, and honest will be formed.